ORGANIZATIONAL INNOVATIONS IN THE ACTIVITIES OF CONSTRUCTION COMPANIES IN UKRAINE IN THE TRANSITION TO WORLD STANDARDS OF MANAGEMENT - Redkin, Oleksandr; Zlepko, Oleksandr; Pents, Maryna (Academic journal Industrial Machine Building Civil Engineering, 2019)
The scientific bases and practical recommendations for the construction enterprises of Ukraine on the progress of their structure and activity through the implementation of organizational and process innovations proposed in this work are considered.Such innovations are developed on the basis of studying and attracting the best world experience, the latest standards of management of construction investment projects, modern forms and methods of corporate management. Implementation of theproposed innovations will improve the quality, timeliness and efficiency of the construction of individual objects, should improve the structure, functions and performance of enterprises of the domestic construction complex, and ultimately - shouldincrease the competitiveness of the economy and social life in new economic conditions.
Keywords: construction and investment projects; improvement of the organizational structure of the enterprise; project management standards